STRUCTURAL SCHEMA OF THE MODEM SYSTEM OF THE MIX PREPARATION PROCESS CONTROL AND QUALITY MANAGEMENT - A. P. Melnikov; M. A. Sajkov; D. M. Golub (Литьë и металлургия)
The constant development of technologies of shaping requires the perfecting of the mix preparation systems including their control.